Prediksi Kebutuhan Ruang Kelas Perguruan Tinggi dengan Pendekatan Dinamika Sistem - Dian Fajarika; Ester Anggi Kristiani; Olivia Anastasia Gultom; Sisean Jansen Pedro Sirait (Jurnal Serambi Engineering, 2025)
The availability of physical infrastructure, particularly classrooms, is a critical component in supporting the quality of academic services in higher education institutions. An imbalance between student enrollment growth and classroom capacity can reduce the effectiveness of learning and student satisfaction. This study aims to design a predictive model for classroom needs using a System Dynamics approach, by examining the interrelationship between student numbers, classroom capacity, and student admission policies at the Institut Teknologi Sumatera. The model was developed through stages including problem identification, system conceptualization using a causal loop diagram, formulation of a stock and flow diagram, and model validation through statistical testing. Simulation results indicate that classroom demand will significantly increase over the next 10 to 20 years, driven by a 2% annual student growth rate. To meet this demand, an annual increase of classroom capacity by 4.49% is required, with an alternative scenario of a 5% annual increase capable of accelerating the fulfillment timeline from 24 years to 13 years. These findings highlight the importance of adaptive and data-driven infrastructure planning as a strategic effort to enhance the quality of academic services in higher education institutions.